Synthetic Cannabinoid Abuse and a Rare Alpha-1-Antitrypsin Mutant Causing Acute Fulminant Hepatitis: A Case Report and Review of the Literature - Kurt J. Knowles; Eric X. Wei; Abhishek Seth; John Bienvenu; James Morris; Kenneth Manas; Paul Jordan; Moheb Boktor (Case Reports in Hepatology)
Synthetic cannabinoids (SCs) abuse is on the rise because they are easily obtained over the counter; they are potent psychoactive compounds and routine drug testing does not detect them. As their abuse is on the rise, so are their detrimental side effects; however, the occurrence of acute hepatitis due to SCs abuse has been reported only once before. In this case, testing revealed that the patient was also heterozygous for alpha-1-antitrypsin (A-1-AT) with the phenotype of PI⁎EM. This mutant phenotype has never been reported as a cause of A-1-AT disease and the abuse of SCs in a patient with this phenotype has also never been reported. This case illustrates the possible need to expand routine drug testing for SCs and consider A-1-AT phenotyping in certain clinical scenarios.